2020
DOI: 10.1287/mnsc.2019.3366
|View full text |Cite
|
Sign up to set email alerts
|

Appointment Scheduling Under Time-Dependent Patient No-Show Behavior

Abstract: This paper studies how to schedule medical appointments with time-dependent patient no-show behavior and random service times. The problem is motivated by our studies of independent datasets from countries in two continents that unanimously identify a significant time-of-day effect on patient show-up probabilities. We deploy a distributionally robust model, which minimizes the worst-case total expected costs of patient waiting and service provider’s idling and overtime, by optimizing the scheduled arrival time… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
37
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 78 publications
(39 citation statements)
references
References 25 publications
2
37
0
Order By: Relevance
“…(2012), Zacharias and Pinedo (2014, 2017) and Kong et al. (2020). A well‐known strategy to offset the impact of no‐shows is overbooking, that is, booking more customers in a certain time slot than the service capacity.…”
Section: Literature Reviewmentioning
confidence: 98%
“…(2012), Zacharias and Pinedo (2014, 2017) and Kong et al. (2020). A well‐known strategy to offset the impact of no‐shows is overbooking, that is, booking more customers in a certain time slot than the service capacity.…”
Section: Literature Reviewmentioning
confidence: 98%
“…Among the studies on outpatient scheduling, the ones that consider (i) patient sequencing (ii) appointment time decisions, or (iii) patient scheduling in a multiple resource setting are relevant to our study. As also pointed out in Ahmadi‐Javid et al (2017), most of the articles assume a predetermined patient sequence due to the complexity of sequencing problem (Begen & Queyranne, 2011; Denton & Gupta, 2003; Kong, Li, Liu, Teo, & Yan, 2020). In the context of single‐server scheduling, only a few articles consider sequencing and time setting decisions simultaneously (Berg, Denton, Erdogan, & Rohleder, 2014; Denton, Viapiano, & Vogl, 2007; Mak, Rong, & Zhang, 2014; Mancilla & Storer, 2012).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Approximately 29% of patients reported receiving responses within 2 hours of a request, which is considered rapid. Numerous studies in the appointment scheduling area have shown the importance of managing waiting time in health care management [45][46][47]. Marketing research has shown that waiting time is a crucial determinant of customer satisfaction and loyalty [48].…”
Section: Main Findings and Comparison With Other Studiesmentioning
confidence: 99%